2011
DOI: 10.5194/acp-11-2423-2011
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, sources, and transport of aerosols measured in spring 2008 during the aerosol, radiation, and cloud processes affecting Arctic Climate (ARCPAC) Project

Abstract: We present an overview of the background, scientific goals, and execution of the Aerosol, Radiation, and Cloud Processes affecting Arctic Climate (ARCPAC) project of April 2008. We then summarize airborne measurements, made in the troposphere of the Alaskan Arctic, of aerosol particle size distributions, composition, and optical properties and discuss the sources and transport of the aerosols. The aerosol data were grouped into four categories based on gas-phase composition. First, the background troposphere c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
305
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 269 publications
(337 citation statements)
references
References 158 publications
(248 reference statements)
22
305
3
Order By: Relevance
“…Indeed, aircraft observations collected during POLARCAT-IPY show elevated PAN and CO concentrations in air masses transported from Asian and North American anthropogenic emission regions in summer 2008 (Law et al, 2014, and references therein). Boreal forest fires are also an important source of PAN and, due to their proximity to the Arctic, plumes can be transported to high latitudes during the spring and summer months (Brock et al, 2011;Singh et al, 2010). Whilst little O 3 production appears to occur close to boreal fires (Alvarado et al, 2010;Paris et al, 2010), several recent studies have shown O 3 production downwind from boreal fires in the Arctic during the summer months (Wespes et al, 2012;Parrington et al, 2012;Thomas et al, 2013).…”
Section: Arcticmentioning
confidence: 99%
“…Indeed, aircraft observations collected during POLARCAT-IPY show elevated PAN and CO concentrations in air masses transported from Asian and North American anthropogenic emission regions in summer 2008 (Law et al, 2014, and references therein). Boreal forest fires are also an important source of PAN and, due to their proximity to the Arctic, plumes can be transported to high latitudes during the spring and summer months (Brock et al, 2011;Singh et al, 2010). Whilst little O 3 production appears to occur close to boreal fires (Alvarado et al, 2010;Paris et al, 2010), several recent studies have shown O 3 production downwind from boreal fires in the Arctic during the summer months (Wespes et al, 2012;Parrington et al, 2012;Thomas et al, 2013).…”
Section: Arcticmentioning
confidence: 99%
“…formation, appearance, and persistence of clouds, which play a significant role in the climate system (Bergstrom et al, 2010;Logan et al, 2010;Lyapustin et al, 2010;Brock et al, 2011;Hansen et al, 2011;Lambe et al, 2011;McFarquhar et al, 2011;Booth et al, 2012).…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…The National Aeronautics and Space Administration (NASA) Arctic Research of the Composition of the Troposphere from Aircraft and Satellites (ARCTAS) campaign occurred in April (ARCTAS-A) and July (ARCTAS-B) of 2008 over the North American Arctic . The spring campaign was conducted in parallel with the National Oceanic and Atmospheric Administration (NOAA) Aerosol Radiation and Cloud Processes affecting Arctic Climate (ARCPAC) campaign (Brock et al, 2011). During these springtime campaigns, several dense biomass burning plumes from agricultural and forest fires in Russia were sampled over the Alaskan and Canadian Arctic (Warneke et al, 2009;Fisher et al, 2010).…”
Section: Introductionmentioning
confidence: 99%